(untitled) (Global Journal of Human-Social Science, 2013)
Based on German experiences, this paper discusses the political economy of climate protection. The objective is to come to a better understanding of why climate change has become one of the main topics at the domestic agenda in some countries, despite the fact that there are obvious free-riding problems resulting in increasing difficulties for international policy coordination. Using a strategic trade policy framework, the paper theoretically discusses the incentives for domestic policymakers to advocate an ambitious climate policy and assesses these incentives empirically with econometric methods.